2014
DOI: 10.1175/wcas-d-12-00045.1
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability of Mediterranean Agricultural Systems to Climate Change: The Example of the Sierra Mágina Olive-Growing Region (Andalusia, Spain). Part II: The Future

Abstract: International audienceThe adaptability of olive-growing systems to climate change is studied in the Sierra Mágina region (Andalusia) using an interdisciplinary approach that evaluates and makes associations across climate, water resources, and socioeconomic strategies. First, the evolution of rainfall and temperature during the twenty-first century is assessed at the local scale using 17 regional climate model (RCM) simulations. A 15%–30% rainfall reduction is expected in the fall combined with a 7%–9% annual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…The processes described by the interviewees and observed in the field contradict some of the previous research regarding technology adoption dynamics (Geels and Schot 2007;Rogers 2003). We found that innovations are sometimes incorporated at the local level to solve local problems, but without altering the entire technological regime, as is the case of chipping, were the innovation is partially adopted to solve stubble burning practical issues (mainly permits).…”
Section: Change To Chippingcontrasting
confidence: 69%
See 1 more Smart Citation
“…The processes described by the interviewees and observed in the field contradict some of the previous research regarding technology adoption dynamics (Geels and Schot 2007;Rogers 2003). We found that innovations are sometimes incorporated at the local level to solve local problems, but without altering the entire technological regime, as is the case of chipping, were the innovation is partially adopted to solve stubble burning practical issues (mainly permits).…”
Section: Change To Chippingcontrasting
confidence: 69%
“…Some authors have focused on the role that social and political contexts play in shaping these practices (Ploeg 2009;Poppe et al 2009). Some others (Rogers 2003;Geels and Schot 2007) have rather focused on the role of technological adoption dynamics. Furthermore, some authors suggest that these changes may respond to environmental challenges, including climate change (Smit and Skinner 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, results show that the climate change footprint might be particularly challenging for agroforestry systems in IP, already under heat and water stress (Acácio et al ., 2009; Tanasijevic et al ., 2014). Relevant socio‐economic sectors linked to, for example, wine vineyards (Fraga et al ., 2017), chestnut production (Pereira et al ., 2011), and olive oil production (olive trees) may also be severely affected (Ponti et al ., 2014; Ronchail et al ., 2014). In fact, the land cover data for 2012 reveals major areas of olive groves in Andalucía, fruit tree, and berry plantations in Murcia and Valencia regions located in the southeast portion of the IP and in Algarve and Alentejo located in southern region of Portugal (Figure 14a).…”
Section: Discussionmentioning
confidence: 99%
“…Settling olive orchards on hill slopes (Tombesi et al, 2007) Variable levels of incidence of pests and diseases (Ponti et al, 2014) Pathogen treatments; Protection of pests' natural enemies; Choice of pest resistant olive Cultivars (Tombesi et al, 2007;Proietti and Regni, 2018) Decrease in annual rainfall Alteration of cultivation areas (Ronchail et al, 2014) Shift in crops (Ronchail et al, 2014) Decrease in summer rainfall Decrease in yield (Musolino et al, 2018;Kahiluoto et al, 2019;Roselló et al, 2019) Increased genetic diversity (Kahiluoto et al, 2019;Roselló et al, 2019) Crop insurance (Gonzalez-Zeas et al, 2014) 2 cropping systems, because the production of durum wheat in Europe is mainly concentrated in a few Mediterranean countries (Italy, Spain, France, Macedonia, Greece, Portugal, Cyprus, and Malta), all of which have similar climatic conditions (Ventrella et al, 2012;Ranieri, 2015;Moriondo et al, 2016). In these areas, the yield response indicates declining resilience to increasing temperatures, potentially due to continuously homogenizing and declining cultivars or genetic pool (Kahiluoto et al, 2019;Roselló et al, 2019).…”
Section: Changes In Temperaturementioning
confidence: 99%